2021
DOI: 10.1002/mde.3439
|View full text |Cite
|
Sign up to set email alerts
|

Can pay‐performance sensitivity cure zombie firms? Evidence from China

Abstract: The proper disposal of zombie firms is the key to supply‐side structural reform. Based on data of A‐share markets from 2009 to 2018, this study explores the impact of pay‐performance sensitivity (PPS) of executives on curing zombie firms. The findings show that PPS has a significant effect on curing zombie firms, and the innovation performance plays a partially mediating role between PPS and cured zombie firms. Further analysis shows that the above effects are heterogeneous, demonstrating that the effects of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It has also been observed that the strong competition among banks can reduce zombie formation because banks will have to focus more on due diligence and find highly credit-worthy borrowers (Zhang & Huang, 2022). To reduce agent-principal misalignment, Wu and Pan (2022) analyzed Pay–Performance Sensitivity (PPS), a policy that links managers’ incentives to firm performance. This encourages managers to improve their firm’s competitiveness and make better financing and investment decisions.…”
Section: Findings From Literaturementioning
confidence: 99%
“…It has also been observed that the strong competition among banks can reduce zombie formation because banks will have to focus more on due diligence and find highly credit-worthy borrowers (Zhang & Huang, 2022). To reduce agent-principal misalignment, Wu and Pan (2022) analyzed Pay–Performance Sensitivity (PPS), a policy that links managers’ incentives to firm performance. This encourages managers to improve their firm’s competitiveness and make better financing and investment decisions.…”
Section: Findings From Literaturementioning
confidence: 99%
“…As usual, zombie banking is one of the pillars of corporate zombification, although direct state involvement seems to be a significant driver of zombification through subsidies, guarantees, and government favor (Chang et al, 2021;Jiang et al, 2017;Wu & Pan, 2022).…”
Section: Zombie Firms: International Perspectivesmentioning
confidence: 99%
“…Indeed, over 70% of SOEs would be zombies in China, while above 60% concentrate on the manufacturing sector (Wang & Zhu, 2021). As usual, zombie banking is one of the pillars of corporate zombification, although direct state involvement seems to be a significant driver of zombification through subsidies, guarantees, and government favor (Chang et al, 2021; Jiang et al, 2017; Wu & Pan, 2022).…”
Section: Zombification and Malinvestmentmentioning
confidence: 99%
“…The external environment level includes the development of FinTech (Jin et al, 2022), investor attention (Lin and Zhang, 2023), and fierce bank competition (Zhang and Huang, 2022), and so forth. The enterprise's efforts include downsizing and restructuring (Carreira et al, 2021), increasing the proportion of female executives (Fang et al, 2020), and improving pay‐performance sensitivity (Wu and Pan, 2021), and so forth.…”
Section: Introductionmentioning
confidence: 99%